Pengaruh Kompensasi dan Work-Life Balance Terhadap Intention To Stay: Lingkungan Kerja Sebagai Mediator - Anggry Pramesti; Fitri Wulandari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigates the role of work setting as a mediator between pay, work-life balance, and intention to stay. This study surveyed sixty employees of PT PLN UP3 Klaten using a census-style methodology. To do quantitative analysis, we collected data from an online poll and then sent it via the PLS-SEM algorithm in SmartPLS 4.0. Compensation and work-life balance were shown to have a substantial influence on intention to remain. The workplace acts as a mediator between workers' intentions to remain and factors like pay and work-life balance. Increases in both direct and indirect compensation create a more positive work environment, which in turn increases the likelihood that employees will stay around. Adding to the body of knowledge, this study demonstrates that a pleasant workplace reinforces the correlation between pay, work-life balance, and intention to stay. Companies may improve employee retention by enhancing work-life balance and compensation plans.